Perioperative frailty: lessons learned and future directions. Issue 3 (June 2021) - Adeleke, Ibukunoluwa; Blitz, Jeanna
Abstract : Purpose of review: As the surgical population ages, preoperative diagnosis and optimization of frailty becomes increasingly important. Various concepts are used to define frailty, and several tools have been validated for use in the perioperative period. This article reviews current conceptual frameworks of frailty, references current literature and provides a practical approach to the preoperative frailty assessment with a focus on potential interventions. Recent findings: A multipronged approach toward preoperative optimization should be used in patients with frailty syndrome. Oral protein supplementation and immunonutrition therapy can reduce complications in patients with malnutrition. Initiating a preoperative physical exercise regimen may mitigate frailty. Nonpharmacologic interventions to reduce preoperative anxiety and improve mood are effective, low-cost adjuncts associated with improvement in postoperative outcomes. Engaging in shared decision making is a critical component of the preoperative evaluation of frail patients. Summary: Emerging evidence suggests that frailty may be mitigated with patient-specific, multidimensional preoperative interventions, thus potentially improving postoperative outcomes in this vulnerable patient population.